2019
DOI: 10.3389/fgene.2019.00997
|View full text |Cite
|
Sign up to set email alerts
|

The Camel Adaptive Immune Receptors Repertoire as a Singular Example of Structural and Functional Genomics

Abstract: The adaptive immune receptors repertoire is highly plastic, with its ability to produce antigen-binding molecules and select those with high affinity for their antigen. Species have developed diverse genetic and structural strategies to create their respective repertoires required for their survival in the different environments. Camelids, until now, considered as a case of evolutionary innovation because of their only heavy-chain antibodies, represent a new mammalian model particularly useful for understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 112 publications
(201 reference statements)
1
34
0
Order By: Relevance
“…However, cDNA sequencing clearly revealed that besides the combinatorial diversity and the introduction of N region diversity typical of all known IG and TR genes, a further mechanism enhances the TRG diversity in Camelus dromedarius . In line with previous reports [ 97 ], more recent studies [ 35 , 98 ] have provided direct evidence that somatic hypermutation (SHM) heavily contributes to the expansion of the γδ TR repertoire even in the absence of functional reiterated genome duplications. The frequency of mutations observed in the V-γ domain was comparable with that found in targeted genes in AID-induced T lymphomas [ 99 ], rearranged shark TRGV [ 71 ], and dromedary TRDV regions [ 100 ].…”
Section: The Trg Locus In Cetartiodactyla and Carnivora: The “Genesupporting
confidence: 82%
See 2 more Smart Citations
“…However, cDNA sequencing clearly revealed that besides the combinatorial diversity and the introduction of N region diversity typical of all known IG and TR genes, a further mechanism enhances the TRG diversity in Camelus dromedarius . In line with previous reports [ 97 ], more recent studies [ 35 , 98 ] have provided direct evidence that somatic hypermutation (SHM) heavily contributes to the expansion of the γδ TR repertoire even in the absence of functional reiterated genome duplications. The frequency of mutations observed in the V-γ domain was comparable with that found in targeted genes in AID-induced T lymphomas [ 99 ], rearranged shark TRGV [ 71 ], and dromedary TRDV regions [ 100 ].…”
Section: The Trg Locus In Cetartiodactyla and Carnivora: The “Genesupporting
confidence: 82%
“…In most mammalian species, including human [ 20 , 21 ], mouse [ 22 ], chimpanzee and rhesus monkey [ 23 ], dog [ 24 ], rabbit [ 25 ], ferret [ 26 ], and cat [ 27 ], two TRBD-J-C clusters exist. In contrast, in the cetartiodactyl lineage [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], a duplication event within the 3′ end of the TRB locus led to the generation of a third TRBD-J-C cluster, increasing the number of TRBD and TRBJ genes available for the somatic rearrangements.…”
Section: The Tr Chains Are Encoded By Separate Multigene Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If ancient gene duplications within the TRB locus led to the generation of the different TRBV subgroups shared among mammals [ 48 ], in ruminants the framework of the TRBV germline repertoire evolved with a more recent expansion of two main TRBV subgroups rather than with the emergence of diverse TRBV subgroups. Overall, this extensive gene expansion resulted in ruminant species (goat, sheep and cattle) possessing a germline TRBV repertoire with the highest number of genes among all the mammalian species studied so far [ 7 , 11 ], including other artiodactyl species such as pigs and camels [ 14 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…If ancient gene duplications within the TRB locus led to the generation of the different TRBV subgroups shared among mammals [45], in ruminants the framework of the TRBV germline repertoire evolved with a more recent expansion of two main TRBV subgroups rather than with the emergence of diverse TRBV subgroups. Overall, this extensive gene expansion resulted in ruminant species (goat, sheep and cattle) possessing a germline TRBV repertoire with the highest number of genes among all the mammalian species studied so far [7,11], including other artiodactyl species such as pigs and camels [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%